Analisis User Interface dalam Perancangan Website “Internet” dengan Metode System Usability Scale - Kuntoro, Jonas; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p56, 2022)
User Interface or UI is the appearance of an application, whether it is mobile or website-based. User Interface display can be in the form of writing, shapes, or colors that are attractive to users. An immature User Interface design can make the application run less than optimally and cause users to switch to other more interesting applications. The purpose of this study is to analyze the quality of the User Interface design of the "Internet" website as a Management Information System for interns. Analysis of the quality of the User Interface design will be carried out using the SUS or System Usability Scale method. Quality evaluation on the usability aspect is carried out using the SUS questionnaire as an assessment standard. The results of this assessment will determine whether or not the UI design of the "Internet" website is feasible.